EVALUASI KUALITAS PENGELOLAAN PERPUSTAKAAN SEKOLAH TERHADAP MINAT MEMBACA SISWA DI SEKOLAH MENENGAH KEJURUAN NEGERI 3 ALASA - Zalukhu, Robert Rista Alius; Lahagu, Arianto; Lase , Asali; Telaumbanua, Wahyutra Adilman (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to evaluate the quality of school library management and its impact on students' reading interest at SMK Negeri 3 Alasa. The background of this study is based on the library's important role as a learning resource center that supports the improvement of students' literacy and reading interest. The research method used is a quantitative approach. Data were collected through observation, questionnaires, and interviews with students and library staff. The results of the study indicate that the quality of library management at SMK Negeri 3 Alasa is quite good, both in terms of collection availability, services, facilities and infrastructure, and librarian competence. However, several shortcomings were still found, particularly in terms of updating the book collection and utilizing information technology. Based on data analysis, there is a positive relationship between the quality of library management and the level of student reading interest. The better the library management, the higher the student reading interest. This study recommends improving library facilities, training librarians, and integrating structured literacy programs to encourage a reading culture in schools. With optimal library management, it is hoped that students' interest in reading will continue to increase sustainably.